Audience genre expectations in the age of digital media - Jeffres, Leo W.; Atkin, David J.; Neuendorf, Kimberly A. (Routledge, 2023)
"This volume bridges the divide between film and media studies scholarship by exploring audience expectations of film and TV genre in the age of digital streaming, using qualitative thematic and quantitative data-driven analyses. Through four ground-breaking surveys of audience members and content creators, the authors have empirically determined what audiences expect of various genres, the extent to which these definitions match those of scholars and critics, and the overall variation and complexity of audience expectations in the age of media abundance. They also examine audience habits and preferences, drawing from both theory and original empirical analyses, with a view toward the implications for the moving image in a rapidly changing media environment. The book draws from the data to develop a number of new concepts, including genre repertoire, genre hybridity, audience interest maximization and variety seeking, and a new stage of genre development, genre bending. An ideal resource for students and scholars interested in the symbiotic relationship between audiences and the moving image products they consume, as well as the way the current digital media environment has impacted our understanding of film and TV genres"--